2018
DOI: 10.31958/jt.v21i2.1235
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran English Public Speaking Berbasis Project-Based Learning

Abstract: Learning Public Speaking does not only include good speaking English but also gives attractive performance. However, this is not easy due to the fearness and anxiety with various symptoms such as a rapid heartbeat, wet palms, or vibrating sounds. In order to minimize the obstacles, Project Based Learning (PBL) is designed. The students are assigned to be public speakesr sharing the information about agency programs to public. The project was eventually documented in the form of videos. To find out the success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Then, a study on a female student who was assigned to create recorded public speaking activities found that projects helped her gain more confidence in her performance, such as in using the gesture, eye contact, facial expression, and smile and improve her language in the areas of word stress, rhythm, naturalness, performance from the first project to the second one. Interview with the subject also revealed that she felt more comfortable and relaxed when she performed second video recorded public speaking project (Apriyanti, Sumira, & Sariani, 2019). Finally, the use of video feedback reduced the anxiety of all research participants in public speaking from pre-intervention to post-intervention (Donovan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Then, a study on a female student who was assigned to create recorded public speaking activities found that projects helped her gain more confidence in her performance, such as in using the gesture, eye contact, facial expression, and smile and improve her language in the areas of word stress, rhythm, naturalness, performance from the first project to the second one. Interview with the subject also revealed that she felt more comfortable and relaxed when she performed second video recorded public speaking project (Apriyanti, Sumira, & Sariani, 2019). Finally, the use of video feedback reduced the anxiety of all research participants in public speaking from pre-intervention to post-intervention (Donovan, 2016).…”
Section: Introductionmentioning
confidence: 99%